CONCEPT OF CREATION AND GENETIC PREDICTION OF TECHNOLOGICAL EQUIPMENT OF NEW GENERATIONS - Yu.N. Kuznetsov (International Journal of Innovations in Engineering Research and Technology, 2021)
The results of scientific research by scientists KPI them. Igor Sikorsky during the creation and genetic prediction of the development of machine tools of new generations and their mechanisms using the latest achievements, combined into an interdisciplinary field of knowledge and built on a single structural and systemic approach. The idea was expressed of reviving domestic machine-tool industry through an innovative breakthrough and the implementation of the strategic goal “Get ahead without catching up